Specialised dental services and referral pathways. Issue 12 (December 2021) - Iles, Rebecca; Cheales, Elizabeth
The term 'oral health' not only defines a state of being free from oral and facial pain, diseases and disorders, but alsoencapsulates the impact that such disease may have on an individual's quality of life, considering both the functional (biting, chewing, smiling, speaking) and psychosocial aspects of wellbeing. Despite the well-established relationship between oral health and overall health and wellbeing, the separation of medicine and dentistry, both educationally and organisationally, results in unmet health needs and poorer patient outcomes. This article aims to give an overview of available dental services, referral pathways and how general practitioner and dentists can work together to provide holistic, patient-centred care.